Performance Analysis of Ujung Serdang Village Office Employees Using the Multi Factor Evaluation Process Method - Nera Mayana Br Tarigan; Sinaga, Bosker; Siregar, Nurika Sari; Parastia, Devina (Cattleya Darmaya Fortuna, 2025)
The final report of this research aims to examine employee performance at the Ujung Serdang Village Office using the Multi Factor Evaluation Process (MFEP) method. Improving the quality of public services in villages is largely determined by the performance of the apparatus involved, considering their role as the front guard in serving the community. However, various factors such as discipline, competence, productivity and technological adaptability often influence employee performance, so a comprehensive and systematic evaluation is needed. Research Method, namely the survey research method, is a research method carried out using surveys or data collection through research respondents. The method used to analyze the data is the Multi Factor Evaluation Process Method. The purpose of this research is to apply and find out the results of the Multi Factor Evaluation Process Method analysis in the Performance Analysis of Ujung Serdang Village Office Employees. The research results show accurate calculations with relevant assessments where values ​​with a difference of 0.01 are shown in the assessment process. From the assessment calculation process, the highest score obtained by alternative 05 was with an Evaluation Weight Value of 94.35. The research conclusion is that the MFEP method is effective in evaluating employee performance because it is able to consider various important factors in a structured manner.